Sams teach yourself Objective-C in 24 hours - Feiler, Jesse (Sams Pub., 2012)
In just 24 sessions of one hour or less, you can master the Objective-C language, and start using it to write powerful native applications for both Macs and iOS devices! Using this book's straightforward, step-by-step approach, you'll get comfortable with Objective-C's unique capabilities ... make the most of its powerful implementation of objects and messaging ... work effectively with design patterns, collections, blocks, threading, and a whole lot more. Every lesson builds on what you've already learned, giving you a rock-solid foundation for real-world success! Step-by-Step Instructions carefully walk you through the most common Objective-C development tasks. Quizzes and Exercises at the end of each chapter help you test your knowledge. By the Way notes present information related to the discussion. Did You Know? tips offer advice or show you easier ways to perform tasks. Watch Out! cautions alert you to possible problems and give you advice on how to avoid them. Printed in full color--figures and code appear as they do in Xcode Use Xcode to write Objective-C software more quickly and efficiently Master Objective-C's object-oriented features and techniques Efficiently organize program files and projects Make the most of Objective-C's powerful messaging capabilities Declare classes, instance variables, properties, methods, and actions Leverage building block patterns to write more powerful code Work with mutable and immutable data types Organize data with collections, including dictionaries and sets Manage memory the modern way, with Automatic Reference Counting (ARC) Expand and extend classes with protocols, delegates, categories, and extensions Apply recent language enhancements such as Associative References and Fast Enumeration Create and work with portable, anonymous code blocks Manage queues and threading with Grand Central Dispatch.